Optical digital to analog conversion performance analysis for indoor set-up conditions - Dobesch, Ales
In visible light communication (VLC) the optical digital to analog conversion (ODAC) approach was proposed as a suitable driving technique able to overcome light-emitting diode’s (LED) non-linear characteristic. This concept is analogous to an electrical digital-to-analog converter (EDAC). In other words, digital bits are binary weighted to represent an analog signal. The method supports elementary on–off based modulations able to exploit the essence of LED’s non-linear characteristic allowing simultaneous lighting and communication. In the ODAC concept the reconstruction error does not simply rely upon the converter bit depth as in case of EDAC. It rather depends on communication system set-up and geometrical relation between emitter and receiver as well. The paper describes simulation results presenting the ODAC’s error performance taking into account: the optical channel, the LED’s half power angle (HPA) and the receiver field of view (FOV). The set-up under consideration examines indoor conditions for a square room with 4mlength and 3mheight, operating with one dominant wavelength (blue) and having walls with a reflection coefficient of 0.8. The achieved results reveal that reconstruction error increases for higher data rates as a result of interference due to multipath propagation.